HUBUNGAN INTENSITAS PENGGUNAAN MEDIA SOSIAL INSTAGRAM TERHADAP AKHLAK MAHASISWA - Misroji; Rahma Syarifah (El-Hikmah: Jurnal Ilmu Dakwah dan Komunikasi, 2024)
Accessing social media makes it easier for users to get information quickly, for example: Instagram, lots of information about positive and negative things on Instagram social media. The intensity of using social media is a picture of how long and how often a person uses social media so that characters are formed in communicating and interacting. Morals are an aspect that is very concerned about both in the world of education and social life, as STIDDI Al-Hikmah Jakarta students should use social media Instagram and other social media properly and correctly.The purpose of this study was to find out how big the relationship between the intensity of Instagram social media usage and the morals of STIDDI AL-Hikmah Jakarta students. This study used a quantitative research type. version 22 and Microsoft excel. Dadal analysis in this study used the normality test, simple linear regression test, correlation coefficient test, and coefficient of determination test. The results of this study indicate that ho is accepted, which means that there is no influence in the relationship between the intensity of the use of Instagram social media on the morals of STIDDI Al-Hikmah Jakarta students. It can also be seen in the Keofessen test of determination, where the R-square is 0.941 ± 0.05, which means that Ho is accepted and Ha is rejected, which states that there is no effect of the relationship between the two. The product moment correlation value shows -0.008 which means it is negative and has a strong level of relationship. which is very weak, because it gets a value of 0.00-0.199.